2004
DOI: 10.1002/eji.200324760
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids induce Fas(CD95) ligand cell surface expression via RARγ and nur77 in T cells

Abstract: Cells from the CD4 + murine T hybridoma line IP-12-7 enter the apoptotic suicide program via the Fas ligand (FasL)/Fas-mediated pathway upon TCR stimulation. This stimulus regulates the sensitization of the Fas death pathway and the cell surface appearance of preformed FasL. The apoptosis is dependent on new mRNA and protein synthesis and involves upregulation of nur77. Two groups of nuclear receptors for retinoic acids (RA) have been identified: retinoic acid receptors (RAR) and retinoid X receptors. IP-12-7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…It is possible that our Western blot analysis was not sensitive enough to detect RAR-␥, although RNA levels for RAR-␣ and RAR-␥ were similar. Other investigators report the presence of RAR-␥ mRNA in T lymphocytes and biological activity for RAR-␥-selective ligands (24). To our knowledge, RAR-␥ protein has not been identified in T lymphocytes by Western blot analysis, thus the significance of RAR-␥ RNA levels in these cells remains uncertain.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is possible that our Western blot analysis was not sensitive enough to detect RAR-␥, although RNA levels for RAR-␣ and RAR-␥ were similar. Other investigators report the presence of RAR-␥ mRNA in T lymphocytes and biological activity for RAR-␥-selective ligands (24). To our knowledge, RAR-␥ protein has not been identified in T lymphocytes by Western blot analysis, thus the significance of RAR-␥ RNA levels in these cells remains uncertain.…”
Section: Discussionmentioning
confidence: 87%
“…For example, retinoic acid and RAR-selective ligands can inhibit Fas-mediated apoptosis by diminishing cell surface Fas ligand expression in T cell hybridomas activated via the TCR (19 -22). This antiapoptotic effect is mediated via RAR-␣/ RXR heterodimers (23), whereas RAR-␥ agonists can up-regulate FAS-ligand and thus facilitate apoptosis in T cell hybridomas (24) as well as thymocytes (25). Thymocyte apoptosis has also been reduced by retinoic acid treatment (26).…”
mentioning
confidence: 99%
“…In the second case, RA counteracts the ability of mitogens to induce FasL and thereby, Fas-induced apoptosis. In the absence of mitogens or other T cell-stimulatory agents, however, it was reported that RA rather enhances than reduces FasL cell-surface expression in hybridoma and preactivated T cells [74]. Thus, it appears that depending on the conditions and the type of T cell, RA will act to repress or promote Fas-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, CD437 increased the levels of death receptors, such as TRAIL receptors, DR4, DR5 and Fas, in human tumor cell lines [19,21,23,35]. CD437 increased the expression of FasL at cell surface of T cells [32], but apoptosis was only partially blocked by FasFc which inhibits Fas-FasL interaction or by an RARg antagonist. As a result, the authors concluded that CD437-induced apoptosis was not correlated to the Fas pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The nur77 gene was shown to be induced by CD437 in a study of CD437-induced changes in gene expression carried out by cDNA array screening in human lung carcinoma cells [31]. The up-regulation of nur77 and FasL induced by CD437 in murine T cells was mediated by RARg [32]. However, these authors also showed that CD437 induced apoptosis via an alternative pathway, which was independent of RARg, nur77 and FasL.…”
Section: Introductionmentioning
confidence: 99%